Keratocystic odontogenic tumor and its radiological diagnosis by 3 dimensional Cone Beam Computed Tomography (CBCT) - Banik, Shoma; Banik, Samir; Shaikh, Mushfiq H; Sadat, SM Anowar; Mallick, Parimal Chandra (Update Dental College Journal, 2013)
Keratocystic odontogenic tumor is a special type of odontogenic cyst. Frequent recurrence after surgical removal, world health organization termed it as a tumor instead of cyst. It is a real challenge for oral and maxillofacial surgeon to deal with this tumor. To manage this tumor, a detailed radiological diagnosis may be of a great help to prevent recurrence. In this presented case, we used Cone beam computed tomography to find out the margin of the extension of cortical perforation diameter of the lesion and type of bone destruction. DOI: http://dx.doi.org/10.3329/updcj.v1i1.13947 Update Dent. Coll. j: 2011; 1 (1): 10-13